Method for preparing high-strength rainproof tarpaulin by recycling waste textiles
By using materials such as modified polyamide and self-repair capsules in waterproof tarpaulins and hybrid chain segment structures, the problem of insufficient waterproof performance and self-repair performance of existing waterproof tarpaulins is solved, significantly improving the waterproof and self-repair performance of the material, and extending the use time.
Patent Information
- Application Number
- CN202411724378.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The waterproof performance and self-repair performance of existing waterproof tarpaulins need to be further improved, especially the wear resistance of the self-repair polyurethane layer is poor, resulting in insufficient self-repair capability and insufficient waterproof performance.
Phosphorylated polyamides are prepared by reacting modified polyamides, 9,10-dihydro-9-oxa-10-phosphophenophen-10-oxides, aluminum chloride and dimethyl sulfoxide under specific conditions, and combined with self-healing capsules, modified capsules and inorganic cross-linking agents and other technologies to hybridize the segment structure of the modified polyamide and impregnation liquid to enhance the waterproof and self-healing properties of the material.
It significantly improves the waterproof ability and self-repairing performance of the waterproof tarp, enhances the material's ultraviolet resistance and flame retardant performance, and extends the use time of the tarp.
Smart Images

Figure BDA0005158836500000031 
Figure BDA0005158836500000041 
Figure BDA0005158836500000051
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of waterproof material processing, and in particular to a method for preparing a high-strength rainproof tarpaulin by recycling waste textiles. Background Art
[0002] The self-healing and waterproof properties of waterproof tarpaulins are constantly improving with the development of materials science. From traditional coated tarpaulins to modern polymer composite materials, the improvement of waterproof performance mainly depends on the combination of surface hydrophobic coatings and high-strength substrates. In recent years, the introduction of self-healing functions has become a new trend. By introducing dynamic chemical bonds or microcapsule technology into the tarpaulin, it can heal quickly after being damaged. The application of nanotechnology also makes the surface of the tarpaulin have super-hydrophobic properties, further improving its waterproof performance. In addition, the development of smart materials allows tarpaulins to dynamically adjust their repair capabilities and waterproof performance in different environments, providing more reliable protection for applications in extreme weather conditions. Waterproof tarpaulins are rapidly evolving from simple durability to high-tech functionality and environmental adaptability.
[0003] Prior art CN117586710A discloses a method for preparing a composite waterproof roll with a self-repairable surface layer, wherein a self-repairable waterborne polyurethane emulsion is roller-coated on the upper side of a polyimide film, and a polyurethane layer with self-repairing properties is formed after drying, and a layer of polyurethane layer with self-repairing properties is coated on the upper side of a main waterproof layer, and vacuum cured to form a film, and polyester is arranged on the lower side of the main waterproof layer, and an adhesive layer is added to the lower side of a polyester cloth layer, thereby preparing a composite waterproof roll with a self-repairable surface layer; a low-bond-energy dynamic diselenide bond is introduced into the main chain of the surface polyurethane film, so as to endow the polyurethane film with self-repairing function and anti-oxidation performance under mild conditions and the ability to self-repair multiple times;
[0004] However, the above patent is to prepare polyimide, apply a self-repairing polyurethane layer on its surface, further set a waterproof layer and then set a self-repairing polyurethane layer to obtain a waterproof membrane; however, once cracks appear in the self-repairing polyurethane layer, repairing the cracks requires cumbersome processes such as cleaning and pressing, and has the disadvantages of poor self-healing property and easy rupture along old scars, resulting in poor wear resistance of the surface self-repairing polyurethane layer, which leads to excessive consumption of the self-repairing layer. The self-repairing ability of the material needs to be further improved, and the hierarchical structure is bonded by direct cooling and drying, lacks cross-linking structure and chemical bonds, resulting in weak bonding ability between the hierarchical structures, which in turn leads to the need for further improvement of the waterproof performance of the material.
[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0006] The purpose of the present invention is to provide a method for recycling waste textiles to prepare high-strength rainproof tarpaulins, which is used to solve the technical problem in the prior art that the waterproof performance and self-repairing performance of waterproof tarpaulins need to be further improved.
[0007] The purpose of the present invention can be achieved by the following technical solution: A method for recycling waste textiles to prepare high-strength rainproof tarpaulin, comprising the following steps:
[0008] S1. Add modified polyamide, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, aluminum chloride and dimethyl sulfoxide into a reactor, raise the temperature of the reactor to 30-50° C., keep the temperature for 1-3 hours, post-treat to obtain phosphated polyamide, and then prepare a waterproof base fabric based on the phosphated polyamide through melt spinning, twisting, warping and weaving;
[0009] The reaction equation for preparing phosphated polyamide is:
[0010]
[0011] Where:
[0012] The reaction principle for preparing phosphated polyamide is as follows: under the catalytic action of high temperature and catalyst, the phosphorus-hydrogen bond on 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and the double bond on the modified polyamide undergo addition reaction, and finally the phosphated polyamide is prepared.
[0013] S2, adding self-repairing capsules, 3-(methacryloyloxy)propyltrimethoxysilane, sodium hydroxide and deionized water into a reactor, raising the temperature of the reactor to 30-50° C., maintaining the temperature for 3-5 hours, and post-treating to obtain modified capsules;
[0014] The reaction principle for preparing the modified capsules is as follows: under the catalysis of alkaline conditions, the siloxy groups on 3-(methacryloyloxy)propyltrimethoxysilane undergo hydrolysis reaction to produce silanol structures, and undergo elimination reaction with the hydroxyl groups on the surface of the self-healing capsules, and finally the modified capsules are prepared.
[0015] S3, adding 2-(perfluorohexyl)ethyl methacrylate, acrylic acid, triphenylethylene, modified capsules, azobisisobutyronitrile and dimethyl sulfoxide into a reaction kettle, raising the temperature of the reaction kettle to 70-80° C., keeping the temperature for reaction for 2-4 hours, and post-treating to obtain an impregnation solution;
[0016] The reaction equation for preparing the impregnation solution is:
[0017]
[0018] Where:
[0019] The reaction principle for preparing the impregnation solution is: under the catalysis of free radical initiator and high temperature, the double bonds on 2-(perfluorohexyl)ethyl methacrylate, acrylic acid, triphenylethylene and modified capsules are broken, and free radical addition reaction occurs, and finally the impregnation solution is prepared.
[0020] S4, immersing the waterproof base fabric into the modified waterproof coating, performing dip-rolling modification, and post-processing to obtain the waterproof tarpaulin.
[0021] Furthermore, in step S1, the amount ratio of modified polyamide, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, aluminum chloride and dimethyl sulfoxide is 8-10g:2-3g:0.3-0.5g:30-50mL, and the post-treatment includes: after the reaction is completed, the reactor is cooled to room temperature, the reaction solution is added to a rotary evaporator with a water bath temperature of 80-100°C, and the reduced pressure distillation is performed until no liquid is extracted to obtain phosphated polyamide; in step S2, the amount ratio of self-repairing capsules, 3-(methacryloyloxy)propyltrimethoxysilane, sodium hydroxide and deionized water is 8-10g:2-3g:0.3-0.5g:30-50mL, and the post-treatment includes: after the reaction is completed, the reaction solution is filtered, the filter cake is collected, and after washing with anhydrous ethanol and deionized water for 3-5 times, the filter cake is placed in a drying oven at a temperature of 60°C for vacuum drying to obtain modified capsules.
[0022] Furthermore, in step S3, the dosage ratio of 2-(perfluorohexyl)ethyl methacrylate, acrylic acid, triphenylethylene, modified capsules, azobisisobutyronitrile and dimethyl sulfoxide is 5-8g:3-5g:2-3g:3-4g:0.5-0.8g:40-60mL, and the post-treatment includes: after the reaction is completed, the reactor is cooled to room temperature, the reaction solution is added to a rotary evaporator with a water bath temperature of 80-100°C, and the reduced pressure distillation is performed until no liquid is extracted to obtain an impregnation solution; in step S4, the modified waterproof coating is prepared by mixing the impregnation solution and azobisisobutyronitrile in a dosage ratio of 8-10mL:0.5-0.8g, the dip-rolling modification operation is a two-dip and two-rolling process, the bath ratio is 1:20-25, and the dip-rolling rate is 90-110%, and the post-treatment includes: after the dip-rolling is completed, the material is placed in a drying oven at a temperature of 80-120°C and vacuum dried until the material has a constant weight to obtain a waterproof tarpaulin.
[0023] Furthermore, in step S1, the preparation method of the modified polyamide comprises the following steps:
[0024] A1. Add waste textiles into a pulverizer and grind them, then pass through a 400-600 mesh screen to obtain powder to be recycled;
[0025] A2, adding the powder to be recycled, 2-vinyl-4,6-diamino-1,3,5-triazine, aluminum hydroxide and N,N-dimethylformamide into a high-pressure reactor, introducing nitrogen protection, raising the temperature of the reactor to 80-120°C, keeping the temperature for reaction for 2-4h, and post-treating to obtain the aminolysis fragment;
[0026] The reaction equation for preparing the aminolysis segment is:
[0027]
[0028] Where:
[0029] The reaction principle for preparing the aminolysis segment is as follows: under high temperature catalysis and protection of inert gas, the polyurethane segment undergoes an aminolysis reaction with 2-vinyl-4,6-diamino-1,3,5-triazine to finally prepare the aminolysis segment.
[0030] A3. Add the aminolysis segment, fumaric acid, inorganic crosslinking agent, N,N'-dicyclohexylcarbodiimide, triethylamine and dimethyl sulfoxide into the reactor, increase the temperature of the reactor to 150-160°C, keep the reaction temperature for 1-2 hours, and post-treat to obtain modified polyamide.
[0031] The reaction equation for preparing modified polyamide is:
[0032]
[0033] Where:
[0034] The reaction principle for preparing modified polyamide is: under the catalysis of catalyst and high temperature, the amino groups on the surface of the inorganic crosslinking agent and the fumaric acid undergo polymerization reaction, and finally the modified polyamide is prepared.
[0035] Further, in step A2, the amount ratio of the powder to be recovered, 2-vinyl-4,6-diamino-1,3,5-triazine, aluminum hydroxide and N,N-dimethylformamide is 8-10g:2-3g:0.3-0.5g:40-60mL, and the post-treatment includes: after the reaction is completed, the reactor is cooled to room temperature, the reaction solution is added to a rotary evaporator with a water bath temperature of 80-100°C, and the reduced pressure distillation is carried out until no liquid is produced to obtain an aminolysis segment; step In A3, the amount ratio of the aminolysis segment, fumaric acid, inorganic crosslinking agent, N,N'-dicyclohexylcarbodiimide, triethylamine and dimethyl sulfoxide is 5-8g:3-5g:2-3g:0.3-0.5g:0.5-0.8g:40-60mL, and the post-treatment includes: after the reaction is completed, the reactor is cooled to room temperature, the reaction liquid is added to a rotary evaporator with a water bath temperature of 80-100°C, and distilled under reduced pressure until no liquid is extracted to obtain a modified polyamide.
[0036] Furthermore, the preparation method of the inorganic crosslinking agent comprises the following steps:
[0037] B1. Add zinc acetate dihydrate, ethanol and polyvinyl pyrrolidone into a reaction kettle, stir at room temperature for 20-30 minutes, adjust the pH value of the reaction system to 9-10 with protective ammonia water, continue stirring for 30-40 minutes to obtain a modified gel, and post-treat the nano zinc oxide particles;
[0038] B2. Add nano zinc oxide particles, 3-aminopropyltriethoxysilane, sodium hydroxide and deionized water into a reactor, increase the temperature of the reactor to 30-50° C., keep the temperature for 3-5 hours, and post-treat to obtain an inorganic cross-linking agent.
[0039] The reaction principle for preparing the inorganic crosslinking agent is as follows: zinc acetate is hydrolyzed under alkaline conditions, and after static aging, nano zinc oxide particles are prepared by high-temperature calcination, and the siloxy structure of 3-aminopropyltriethoxysilane is hydrolyzed under alkaline conditions to produce a silanol structure, which undergoes an elimination reaction with the hydroxyl groups on the surface of the nano zinc oxide particles, and finally an inorganic crosslinking agent is prepared.
[0040] Furthermore, in step B1, the dosage ratio of zinc acetate dihydrate, ethanol and polyvinyl pyrrolidone is 3-5g:15-20mL:0.3-0.5g, and the post-treatment includes: adding the modified gel into a tubular furnace, introducing nitrogen protection, heating the tubular furnace to 450-500°C at a heating rate of 5°C / min, keeping warm and calcining for 4-6h, and then placing the material in a grinder to grind to obtain nano zinc oxide particles; in step B3, the dosage ratio of nano zinc oxide particles, 3-aminopropyltriethoxysilane, sodium hydroxide and deionized water is 8-10g:2-3g:0.3-0.5g:40-60mL, and the post-treatment includes: filtering the reaction solution, collecting the filter cake, washing it with anhydrous ethanol and deionized water for 3-5 times, and then placing the filter cake in a drying oven at a temperature of 60°C for vacuum drying to obtain an inorganic crosslinking agent.
[0041] Furthermore, in step S2, the method for preparing the self-repairing capsule comprises the following steps:
[0042] C1, adding 3-(methacryloyloxy)propyltrimethoxysilane, 3-amino-4,4,4-trifluorocrotonic acid ethyl ester, benzoin, 2,4,6-trimethylbenzoyldiphenylphosphine oxide and tetraethyl orthosilicate into a reaction kettle and stirring for 5-10 minutes to obtain a modified oil phase solution;
[0043] C2, adding the modified oil phase solution into a high-speed homogenizer, and pouring the modified liquid into the modified oil phase solution, setting the speed of the high-speed homogenizer to 8000-9000 rpm, stirring at room temperature for 20-30 minutes, to obtain a modified emulsion;
[0044] C3. Add the modified emulsion into the reactor and stir. Add 1-2 mol / L hydrochloric acid solution into the reactor to adjust the pH value of the system to 4-5. Raise the temperature of the reactor to 40-50°C. After keeping the temperature for 3-4 hours, add the supplement into the reactor. After keeping the temperature for 3-4 hours, add the supplement again. Keep the temperature for 8-12 hours. After post-treatment, obtain the self-repairing capsule.
[0045] The reaction principle for preparing self-repairing capsules is as follows: after pouring the modified liquid into the modified oil phase solution and stirring at high speed, the reaction system produces a water-in-oil structure. After adjusting the pH of the system, the tetraethyl orthosilicate in the oil phase solution is hydrolyzed at the interface between the water and oil phases and finally hydrolyzed on the surface of the oil phase droplets to produce a stable cross-linked structure. After adding the supplement, a stable dense structure is further formed on the capsule surface, and finally a self-repairing capsule is prepared.
[0046] Further, in step C1, the amount ratio of 3-(methacryloyloxy)propyltrimethoxysilane, 3-amino-4,4,4-trifluorocrotonic acid ethyl ester, benzoin, 2,4,6-trimethylbenzoyldiphenylphosphine oxide and tetraethyl orthosilicate is 5-8g:3-5g:0.3-0.5g:0.3-0.5g:20-30mL; in step C2, the amount ratio of modified oil phase solution and modified liquid is 2-3g:10-15mL, and the modified liquid The self-repairing capsule is prepared by preparing fatty alcohol polyoxyethylene ether and deionized water in a dosage ratio of 1-2g:30-40mL; in step C3, the dosage ratio of the modified emulsion hydrochloric acid solution and the supplement is 40mL:3-5mL, the dosage ratio of the supplement added twice is 1:1, and the supplement is tetraethyl orthosilicate. Post-treatment includes: filtering the reaction liquid, collecting the filter cake, washing it with anhydrous ethanol and deionized water for 3-5 times, and placing the filter cake in a drying oven at a temperature of 60°C for vacuum drying to obtain a self-repairing capsule.
[0047] Furthermore, in step S1, the method for preparing the waterproof base fabric comprises the following steps:
[0048] D1, adding the phosphated polyamide and auxiliary materials into a twin-screw extruder for melt extrusion, and then extruding through a spinneret to obtain modified filaments;
[0049] D2, twisting the modified filaments to obtain modified twisted yarns, and warping the modified twisted yarns to obtain modified warp yarns;
[0050] D3, using modified warp yarn for weaving and post-processing to obtain a waterproof base fabric.
[0051] Further, in step D1, the amount ratio of phosphated polyamide and auxiliary materials is 80-100g:30-40g, and the auxiliary materials include: plasticizer, flame retardant, filler and mildew inhibitor, and the amount ratio of plasticizer, flame retardant, filler and mildew inhibitor is 10-12g:6-8g:7-10g:7-10g; in step D2, the twisting process uses a ring spinning machine, the ring speed is 10000-12000r / min, the twist is 60-100 twists / m, the draft multiple is 2-3 times, and the setting The tension range is 8-12N; in step D2, the warping process uses a warping machine frame, the winding speed is 600-800m / min, the warp tension is adjusted to 10-12N, and the pre-wetting humidification rate is 20-30%; in step D3, the weaving uses a high-speed shuttle loom, the loom speed is 500-600r / min, the weft × warp density is 600-1200D, the weft tension is 8-10N, the warp tension is 10-12N, and the fabric density range is 180-200 roots / cm 2 , post-processing includes: after weaving is completed, the material is placed in a heat setting machine, the temperature of the heat setting machine is set to 150-180°C, the setting time is 30-60s, the traction speed is 10-12m / min, and the waterproof base fabric is obtained after setting.
[0052] Furthermore, the plasticizer is one or more of dinonyl phthalate, dioctyl adipate and diisononyl sebacate; the flame retardant is one or more of red phosphorus microcapsules, ammonium polyphosphate and melamine cyanurate; the filler is one or more of glass fiber, silica and carbon fiber; the mildew inhibitor is one or more of zinc pyrithione, benzisothiazolinone and isothiazolinone.
[0053] The present invention has the following beneficial effects:
[0054] 1. The present invention prepares an inorganic cross-linking agent and a modified capsule, and hybridizes the chain segment structure of the modified polyamide and the impregnating liquid respectively, so that the material structure is more compact and the waterproof ability of the material is significantly enhanced. The nano-alumina particles as the inorganic cross-linking agent, while making the modified polyurethane chain segment have a complex spatial structure, work together as a UV absorber and the modified capsule to significantly enhance the UV resistance of the waterproof tarpaulin. The silica shell of the modified capsule also enhances the wear resistance of the material at the same time. The phosphoric acid structure of the modified polyamide chain segment decomposes to produce acidic substances during the combustion process, promotes the carbonization of the triazine ring to form a molten carbon layer, and significantly improves the flame retardant performance of the material. When the waterproof tarpaulin is structurally damaged, the modified capsule releases the repair material and the photoinitiator, and the repair material, the coating chain segment and the modified polyamide undergo polymerization under light, and finally the tarpaulin structure is repaired, thereby extending the service life of the tarpaulin.
[0055] 2. In the preparation of modified polyamide, the present invention selects to perform aminolysis on waste polyurethane textiles. By selecting the aminolysis reagent, a large number of triazine structures are introduced into the segment while retaining the structure of the polyurethane segment, thereby laying a foundation for improving the flame retardant performance of the material; and nano zinc oxide particles with UV resistance are prepared. After being modified with a silane coupling agent to improve its compatibility with the organic structure, the particles are used as a polymerization monomer to polymerize with the aminolysis segment and fumaric acid to prepare the modified polyurethane. By selecting the aminolysis reagent and the polymerization monomer, a large number of double bonds are introduced into the polyurethane segment. The double bond structure introduces the phosphoric acid structure through phosphorus-hydrogen addition, and coordinates with the triazine ring to significantly improve the flame retardant ability of the material. At the same time, the double bond serves as a cross-linking group. During the curing process of the modified waterproof coating, the double bond structure inside the coating is polymerized with the modified polyamide under the catalysis of the free radical initiator to form a compact structure. After structural damage occurs on the surface of the tarpaulin, the double bond structure cooperates with the repair monomer inside the modified capsule to repair the structural damage, thereby improving the service life of the material.
[0056] 3. In the process of preparing the modified capsules of the present invention, a water-insoluble photoinitiator and a repair monomer are selected before preparing the emulsion to ensure the repair ability of the modified capsules to the material under humid conditions, and under the premise that the photoinitiator promotes the polymerization of the repair monomer, a repair monomer 3-amino-4,4,4-trifluorocrotonic acid ethyl ester is selected that has a promoting effect on the initiation performance of the photoinitiator benzoin, and the coordinated cooperation of the photoinitiator and the repair monomer enables the repair ability of the modified capsules to be significantly improved; in the process of preparing the modified capsules, the capsules are modified with a silane coupling agent, which significantly enhances the compatibility of the material with organic matter and introduces a large number of double bonds on the surface thereof, and is closely combined with the organic structure during the preparation of the impregnation solution and the curing of the modified waterproof coating, hybridizing the spatial structure of the organic chain segments and significantly enhancing the wear resistance of the material, thereby significantly improving the wear resistance and self-repairing performance of the waterproof tarpaulin. DETAILED DESCRIPTION
[0057] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0058] Example 1
[0059] The present embodiment provides a method for recycling waste textiles to prepare a high-strength rainproof tarpaulin, comprising the following steps:
[0060] S1. Preparation of phosphated polyamide
[0061] Weigh: 8.4 g zinc acetate dihydrate, 32.0 mL ethanol and 0.8 g polyvinyl pyrrolidone and add them into a reactor. After stirring at room temperature for 20 min, use protective ammonia water to adjust the pH of the reactant system to 9, continue stirring for 30 min, and post-treat to obtain a modified gel;
[0062] The modified gel was added into a tubular furnace, and after nitrogen protection was introduced, the temperature of the tubular furnace was increased to 450°C at a heating rate of 5°C / min. After calcination for 4 hours, the material was placed in a mill and ground to obtain nano zinc oxide particles.
[0063] Weigh: 18.0 g of nano zinc oxide particles, 5.4 g of 3-aminopropyltriethoxysilane, 0.8 g of sodium hydroxide and 84.0 mL of deionized water are added to a reactor, the temperature of the reactor is raised to 30° C., and the reactor is kept warm for 3 hours. The reaction liquid is filtered, and the filter cake is collected. After washing with anhydrous ethanol and deionized water for 3 times, the filter cake is placed in a drying oven at a temperature of 60° C. and vacuum dried to obtain an inorganic crosslinking agent;
[0064] The waste textiles are added into the pulverizer and crushed, and then passed through a 400 mesh screen to obtain the powder to be recycled;
[0065] Weigh: 16.0g of the powder to be recycled, 5.4g of 2-vinyl-4,6-diamino-1,3,5-triazine, 0.8g of aluminum hydroxide and 84.0mL of N,N-dimethylformamide, add them into a high-pressure reactor, introduce nitrogen protection, raise the temperature of the reactor to 80°C, and keep the temperature for 2h. After the reaction is completed, the reactor is cooled to room temperature, and the reaction liquid is added to a rotary evaporator with a water bath temperature of 80°C, and distilled under reduced pressure until no liquid is produced to obtain an aminolysis segment;
[0066] Weigh: 12.0g of aminolysis segment, 8.4g of fumaric acid, 5.4g of inorganic crosslinking agent, 0.8g of N,N'-dicyclohexylcarbodiimide, 1.2g of triethylamine and 84.0mL of dimethyl sulfoxide and add them into a reactor, raise the temperature of the reactor to 150°C, and keep the temperature for reaction for 1h. After the reaction is completed, cool the reactor to room temperature, add the reaction solution into a rotary evaporator with a water bath temperature of 80°C, and distill under reduced pressure until no liquid is produced to obtain a modified polyamide;
[0067] Weigh: 18.0 g of modified polyamide, 5.4 g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 0.8 g of aluminum chloride and 72.0 mL of dimethyl sulfoxide and add them into a reactor, raise the temperature of the reactor to 30°C, and keep the reaction warm for 1 hour. After the reaction is completed, cool the reactor to room temperature, add the reaction liquid into a rotary evaporator with a water bath temperature of 80°C, and distill under reduced pressure until no liquid is produced to obtain phosphated polyamide.
[0068] S2. Preparation of impregnation solution
[0069] Weigh: 12.0 g 3-(methacryloyloxy)propyltrimethoxysilane, 6.4 g 3-amino-4,4,4-trifluorocrotonic acid ethyl ester, 0.8 g benzoin, 0.8 g 2,4,6-trimethylbenzoyldiphenylphosphine oxide and 42.0 mL tetraethyl orthosilicate, add into a reaction kettle and stir for 5 min to obtain a modified oil phase solution;
[0070] Weigh: 3.2 g fatty alcohol polyoxyethylene ether and 64.0 mL deionized water to prepare a modified solution;
[0071] Weigh: 4.8 g of the modified oil phase solution is added to a high-speed homogenizer, and 24.0 mL of the modified liquid is poured into the modified oil phase solution. The speed of the high-speed homogenizer is set to 8000 rpm, and stirred at room temperature for 20 min to obtain a modified emulsion;
[0072] Weigh: 40.0 mL of the modified latex was added to the reactor and stirred, 1.2 mol / L hydrochloric acid solution was added to the reactor to adjust the system pH to 5, the temperature of the reactor was raised to 40°C, and after the reaction was kept warm for 3 hours, 1.6 mL of tetraethyl orthosilicate was added to the reactor, and the reaction was continued for 3 hours, and then 1.6 mL was added to the reactor again, and the reaction was kept warm for 8 hours. The reaction liquid was filtered, and the filter cake was collected. After washing with anhydrous ethanol and deionized water for 3 times, the filter cake was placed in a drying oven at a temperature of 60°C and vacuum dried to obtain a self-repairing capsule;
[0073] Weigh: 16.0 g of self-repairing capsules, 4.8 g of 3-(methacryloyloxy)propyltrimethoxysilane, 0.8 g of sodium hydroxide and 84.0 mL of deionized water are added to the reactor, the temperature of the reactor is raised to 30°C, and the temperature is kept for 3 hours. After the reaction is completed, the reaction liquid is filtered, and the filter cake is collected. After washing with anhydrous ethanol and deionized water for 3 times, the filter cake is placed in a drying oven at a temperature of 60°C and vacuum dried to obtain a modified capsule;
[0074] Weigh: 12.0g 2-(perfluorohexyl)ethyl methacrylate, 8.4g acrylic acid, 4.8g triphenylethylene, 7.2g modified capsules, 1.2g azobisisobutyronitrile and 84.0mL dimethyl sulfoxide and add them into a reactor, raise the temperature of the reactor to 70°C, and keep the reaction for 2h. After the reaction is completed, cool the reactor to room temperature, add the reaction solution into a rotary evaporator with a water bath temperature of 80°C, and distill under reduced pressure until no liquid is extracted to obtain an impregnation solution.
[0075] S3. Preparation of waterproof tarpaulin
[0076] Weigh: 84.0 g of phosphated polyamide, 10.8 g of dinonyl phthalate, 6.4 g of ammonium polyphosphate, 8.4 g of silicon dioxide and 8.4 g of zinc pyrithione, add them into a twin-screw extruder for melt extrusion, and extrude through a spinneret to obtain modified filaments;
[0077] The modified filaments are neatly arranged on the creel of the ring spinning machine, the ring speed is 10000r / min, the twist is 60 twists / m, the draft multiple is 2 times, the tension range is set to 8N, and the modified twisted yarn is obtained after the twisting is completed;
[0078] The modified twisted yarn is loaded onto the warping machine creel, and after ensuring that the yarns are parallel and not crossed, the winding speed is set to 600 m / min, the warp tension is adjusted to 10 N, the pre-wetting and humidification rate is 20%, and the warping is performed to obtain the modified warp yarn;
[0079] The modified warp yarn was woven using a high-speed shuttle loom with a loom speed of 500 r / min, a weft × warp density of 600D, a weft tension of 8N, a warp tension of 10N, and a fabric density range of 180 yarns / cm 2 After weaving, the material is placed in a heat setting machine, the temperature of the heat setting machine is set to 150°C, the setting time is 30s, and the pulling speed is 10m / min. After setting, a waterproof base fabric is obtained;
[0080] Weigh: 16.0 mL of the impregnation solution and 1.2 g of azobisisobutyronitrile to prepare a modified waterproof coating;
[0081] The waterproof base fabric is immersed in the modified waterproof coating, and a two-immersion and two-rolling process is adopted, with a bath ratio of 1:20 and a immersion and rolling rate of 90%. After the immersion and rolling are completed, the material is placed in a drying oven at a temperature of 80°C and vacuum dried until the material has a constant weight to obtain a waterproof tarpaulin.
[0082] Example 2
[0083] The present embodiment provides a method for recycling waste textiles to prepare a high-strength rainproof tarpaulin, comprising the following steps:
[0084] S1. Preparation of phosphated polyamide
[0085] Weigh: 8.4 g zinc acetate dihydrate, 32.0 mL ethanol and 0.8 g polyvinyl pyrrolidone and add them into a reactor. After stirring at room temperature for 20 min, use protective ammonia water to adjust the pH of the reactant system to 10, continue stirring for 30 min, and post-treat to obtain a modified gel;
[0086] The modified gel was added into a tubular furnace, and after nitrogen protection was introduced, the temperature of the tubular furnace was increased to 500°C at a heating rate of 5°C / min, and after calcination for 6 hours, the material was placed in a mill and ground to obtain nano zinc oxide particles;
[0087] Weigh: 16.0 g of nano zinc oxide particles, 5.4 g of 3-aminopropyltriethoxysilane, 0.8 g of sodium hydroxide and 90.0 mL of deionized water are added to a reactor, the temperature of the reactor is raised to 50° C., and the reactor is kept warm for 5 hours. The reaction liquid is filtered, and the filter cake is collected. After washing with anhydrous ethanol and deionized water for 5 times, the filter cake is placed in a drying oven at a temperature of 60° C. and vacuum dried to obtain an inorganic crosslinking agent;
[0088] The waste textiles are added into the pulverizer and crushed, and then passed through a 600 mesh screen to obtain the powder to be recycled;
[0089] Weigh: 18.0g of the powder to be recycled, 5.4g of 2-vinyl-4,6-diamino-1,3,5-triazine, 0.8g of aluminum hydroxide and 60.0mL of N,N-dimethylformamide, add them into a high-pressure reactor, introduce nitrogen protection, raise the temperature of the reactor to 120°C, and keep the temperature for 4h. After the reaction is completed, the reactor is cooled to room temperature, and the reaction liquid is added to a rotary evaporator with a water bath temperature of 100°C, and distilled under reduced pressure until no liquid is produced to obtain an aminolysis segment;
[0090] Weigh: 12.0g of aminolysis segment, 8.4g of fumaric acid, 5.4g of inorganic crosslinking agent, 0.8g of N,N'-dicyclohexylcarbodiimide, 1.6g of triethylamine and 84.0mL of dimethyl sulfoxide and add them into a reactor, raise the temperature of the reactor to 150°C, and keep the temperature for 2h. After the reaction is completed, cool the reactor to room temperature, add the reaction solution into a rotary evaporator with a water bath temperature of 100°C, and distill under reduced pressure until no liquid is produced to obtain a modified polyamide;
[0091] Weigh: 20.0g modified polyamide, 5.4g 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 0.8g aluminum chloride and 96.0mL dimethyl sulfoxide are added into a reactor, the temperature of the reactor is raised to 50°C, and the reaction is kept warm for 3h. After the reaction is completed, the reactor is cooled to room temperature, and the reaction liquid is added to a rotary evaporator with a water bath temperature of 100°C, and distilled under reduced pressure until no liquid is produced to obtain phosphated polyamide.
[0092] S2. Preparation of impregnation solution
[0093] Weigh: 14.8 g 3-(methacryloyloxy)propyltrimethoxysilane, 8.4 g 3-amino-4,4,4-trifluorocrotonic acid ethyl ester, 0.8 g benzoin, 0.8 g 2,4,6-trimethylbenzoyldiphenylphosphine oxide and 42.0 mL tetraethyl orthosilicate, add into a reaction kettle and stir for 10 min to obtain a modified oil phase solution;
[0094] Weigh: 3.6 g fatty alcohol polyoxyethylene ether and 64.0 mL deionized water to prepare a modified solution;
[0095] Weigh: 5.4 g of the modified oil phase solution is added to a high-speed homogenizer, and 20.0 mL of the modified liquid is poured into the modified oil phase solution. The speed of the high-speed homogenizer is set to 9000 rpm, and stirred at room temperature for 30 min to obtain a modified emulsion;
[0096] Weigh: 80.0mL of modified latex is added to the reactor and stirred, 2.0mol / L hydrochloric acid solution is added to the reactor to adjust the system pH to 4-5, the temperature of the reactor is raised to 40-50°C, and after the reaction is kept warm for 4 hours, 3.2mL of tetraethyl orthosilicate is added to the reactor, and the reaction is continued for 4 hours, and then 3.2mL is added to the reactor, and the reaction is kept warm for 12 hours. The reaction liquid is filtered, and the filter cake is collected. After washing with anhydrous ethanol and deionized water for 5 times, the filter cake is placed in a drying oven at a temperature of 60°C and vacuum dried to obtain a self-repairing capsule;
[0097] Weigh: 18.0 g of self-repairing capsules, 5.4 g of 3-(methacryloyloxy)propyltrimethoxysilane, 0.8 g of sodium hydroxide and 84.0 mL of deionized water are added to the reactor, the temperature of the reactor is raised to 50°C, and the temperature is kept for 5 hours. After the reaction is completed, the reaction liquid is filtered, the filter cake is collected, and after washing with anhydrous ethanol and deionized water for 5 times, the filter cake is placed in a drying oven at a temperature of 60°C and vacuum dried to obtain a modified capsule;
[0098] Weigh: 12.0g 2-(perfluorohexyl)ethyl methacrylate, 8.4g acrylic acid, 5.2g triphenylethylene, 7.2g modified capsules, 1.2g azobisisobutyronitrile and 96.0mL dimethyl sulfoxide and add them into a reactor, raise the temperature of the reactor to 80°C, and keep the reaction for 4h. After the reaction is completed, cool the reactor to room temperature, add the reaction solution into a rotary evaporator with a water bath temperature of 100°C, and distill under reduced pressure until no liquid is extracted to obtain an impregnation solution.
[0099] S3. Preparation of waterproof tarpaulin
[0100] Weigh: 96.0 g of phosphated polyamide, 12.0 g of dinonyl phthalate, 7.2 g of ammonium polyphosphate, 8.4 g of silicon dioxide and 8.4 g of zinc pyrithione, add them into a twin-screw extruder for melt extrusion, extrude through a spinneret, and post-treat to obtain modified filaments;
[0101] The modified filaments are neatly arranged on the creel of the ring spinning machine, the ring speed is 12000r / min, the twist is 100 twists / m, the draft multiple is 3 times, the tension range is set to 12N, and the modified twisted yarn is obtained after the twisting is completed;
[0102] The modified twisted yarn is loaded onto the warping machine creel, and after ensuring that the yarns are parallel and not crossed, the winding speed is set to 800 m / min, the warp tension is adjusted to 12 N, the pre-wetting and humidification rate is 30%, and the warping is performed to obtain the modified warp yarn;
[0103] The modified warp was woven using a high-speed shuttle loom with a loom speed of 600 r / min, a weft × warp density of 1200 D, a weft tension of 10 N, a warp tension of 12 N, and a fabric density range of 200 yarns / cm 2 After weaving, the material is placed in a heat setting machine, the temperature of the heat setting machine is set to 180°C, the setting time is 60s, and the pulling speed is 12m / min. After setting, a waterproof base fabric is obtained;
[0104] Weigh: 16.0 mL of the impregnation solution and 1.6 g of azobisisobutyronitrile to prepare a modified waterproof coating;
[0105] The waterproof base fabric is immersed in the modified waterproof coating, and a two-immersion and two-rolling process is adopted, with a bath ratio of 1:25 and a immersion and rolling rate of 110%. After the immersion and rolling are completed, the material is placed in a drying oven at a temperature of 120°C and vacuum dried until the material has a constant weight to obtain a waterproof tarpaulin.
[0106] Example 3
[0107] The present embodiment provides a method for recycling waste textiles to prepare a high-strength rainproof tarpaulin, comprising the following steps:
[0108] S1. Preparation of phosphated polyamide
[0109] Weigh: 8.4 g zinc acetate dihydrate, 40.0 mL ethanol and 0.8 g polyvinyl pyrrolidone and add them into a reactor, stir at room temperature for 30 min, use protective ammonia water to adjust the pH of the reaction system to 10, continue stirring for 40 min, and post-treat to obtain a modified gel;
[0110] The modified gel was added into a tubular furnace, and after nitrogen protection was introduced, the temperature of the tubular furnace was increased to 475°C at a heating rate of 5°C / min. After calcination for 6 hours, the material was placed in a mill and ground to obtain nano zinc oxide particles.
[0111] Weigh: 18.0 g of nano zinc oxide particles, 5.4 g of 3-aminopropyltriethoxysilane, 0.8 g of sodium hydroxide and 120.0 mL of deionized water are added to a reactor, the temperature of the reactor is raised to 50° C., and the reactor is kept warm for 5 hours. The reaction liquid is filtered, and the filter cake is collected. After washing with anhydrous ethanol and deionized water for 5 times, the filter cake is placed in a drying oven at a temperature of 60° C. and vacuum dried to obtain an inorganic crosslinking agent;
[0112] The waste textiles are added into the pulverizer and crushed, and then passed through a 500 mesh screen to obtain the powder to be recycled;
[0113] Weigh: 18.0 g of the powder to be recycled, 5.4 g of 2-vinyl-4,6-diamino-1,3,5-triazine, 0.8 g of aluminum hydroxide and 84.0 mL of N,N-dimethylformamide, add them into a high-pressure reactor, introduce nitrogen protection, raise the temperature of the reactor to 100° C., and keep the temperature for 2 hours. After the reaction is completed, the reactor is cooled to room temperature, and the reaction liquid is added to a rotary evaporator with a water bath temperature of 100° C., and distilled under reduced pressure until no liquid is produced to obtain an aminolysis segment;
[0114] Weigh: 12.0g of aminolysis segment, 8.4g of fumaric acid, 5.4g of inorganic crosslinking agent, 0.8g of N,N'-dicyclohexylcarbodiimide, 1.2g of triethylamine and 100.0mL of dimethyl sulfoxide and add them into a reactor, raise the temperature of the reactor to 160°C, and keep the temperature for 2h. After the reaction is completed, cool the reactor to room temperature, add the reaction liquid into a rotary evaporator with a water bath temperature of 100°C, and distill under reduced pressure until no liquid is produced to obtain a modified polyamide;
[0115] Weigh: 18.0g modified polyamide, 5.4g 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 0.8g aluminum chloride and 72.0mL dimethyl sulfoxide and add them into a reactor, raise the temperature of the reactor to 50°C, and keep the reaction for 2h. After the reaction is completed, cool the reactor to room temperature, add the reaction liquid into a rotary evaporator with a water bath temperature of 90°C, and distill under reduced pressure until no liquid is produced to obtain phosphated polyamide.
[0116] S2. Preparation of impregnation solution
[0117] Weigh: 14.2 g 3-(methacryloyloxy)propyltrimethoxysilane, 8.4 g 3-amino-4,4,4-trifluorocrotonic acid ethyl ester, 0.8 g benzoin, 0.8 g 2,4,6-trimethylbenzoyldiphenylphosphine oxide and 54.0 mL tetraethyl orthosilicate, add into a reaction kettle and stir for 8 min to obtain a modified oil phase solution;
[0118] Weigh: 1.8 g fatty alcohol polyoxyethylene ether and 36.0 mL deionized water to prepare a modified solution;
[0119] Weigh: 5.4 g of the modified oil phase solution is added to a high-speed homogenizer, and 24.0 mL of the modified liquid is poured into the modified oil phase solution. The speed of the high-speed homogenizer is set to 8500 rpm, and stirred at room temperature for 25 min to obtain a modified emulsion;
[0120] Weigh: 40.0 mL of the modified latex was added to the reactor and stirred, 1.5 mol / L hydrochloric acid solution was added to the reactor to adjust the system pH to 4, the temperature of the reactor was raised to 45°C, and after the reaction was kept warm for 4 hours, 2.4 mL of tetraethyl orthosilicate was added to the reactor, and the reaction was continued for 4 hours, and then 2.4 mL was added to the reactor again, and the reaction was kept warm for 10 hours. The reaction liquid was filtered, and the filter cake was collected. After washing with anhydrous ethanol and deionized water for 5 times, the filter cake was placed in a drying oven at a temperature of 60°C and vacuum dried to obtain a self-repairing capsule;
[0121] Weigh: 18.0 g of self-repairing capsules, 5.4 g of 3-(methacryloyloxy)propyltrimethoxysilane, 0.8 g of sodium hydroxide and 80.0 mL of deionized water are added to the reactor, the temperature of the reactor is raised to 40°C, and the temperature is kept for 4 hours. After the reaction is completed, the reaction liquid is filtered, the filter cake is collected, and after washing with anhydrous ethanol and deionized water for 4 times, the filter cake is placed in a drying oven at a temperature of 60°C and vacuum dried to obtain a modified capsule;
[0122] Weigh: 14.2g 2-(perfluorohexyl)ethyl methacrylate, 8.4g acrylic acid, 5.4g triphenylethylene, 7.2g modified capsules, 1.2g azobisisobutyronitrile and 84.0mL dimethyl sulfoxide and add them into the reactor, raise the temperature of the reactor to 80°C, and keep the reaction for 3h. After the reaction is completed, cool the reactor to room temperature, add the reaction solution into a rotary evaporator with a water bath temperature of 90°C, and distill under reduced pressure until no liquid is extracted to obtain an impregnation solution.
[0123] S3. Preparation of waterproof tarpaulin
[0124] Weigh: 96.0 g of phosphated polyamide, 11.2 g of dinonyl phthalate, 7.2 g of ammonium polyphosphate, 8.4 g of silicon dioxide and 8.4 g of zinc pyrithione, add them into a twin-screw extruder for melt extrusion, extrude through a spinneret, and post-treat to obtain modified filaments;
[0125] The modified filaments are neatly arranged on the creel of the ring spinning machine, the ring speed is 11000r / min, the twist is 80 twists / m, the draft multiple is 3 times, the tension range is set to 10N, and the modified twisted yarn is obtained after the twisting is completed;
[0126] The modified twisted yarn is loaded onto the warping machine creel, and after ensuring that the yarns are parallel and not crossed, the winding speed is set to 700 m / min, the warp tension is adjusted to 10 N, the pre-wetting and humidification rate is 24%, and warping is performed to obtain the modified warp yarn;
[0127] The modified warp was woven using a high-speed shuttle loom with a loom speed of 550 r / min, a weft × warp density of 900 D, a weft tension of 9 N, a warp tension of 11 N, and a fabric density range of 190 strands / cm 2After weaving, the material is placed in a heat setting machine, the temperature of the heat setting machine is set to 160°C, the setting time is 45s, and the pulling speed is 11m / min. After setting, a waterproof base fabric is obtained;
[0128] Weigh: 18.0 mL of the impregnation solution and 1.6 g of azobisisobutyronitrile to prepare a modified waterproof coating;
[0129] The waterproof base fabric is immersed in the modified waterproof coating, and a two-immersion and two-rolling process is adopted, with a bath ratio of 1:24 and a immersion and rolling rate of 100%. After the immersion and rolling are completed, the material is placed in a drying oven at a temperature of 100°C and vacuum dried until the material has a constant weight to obtain a waterproof tarpaulin.
[0130] Comparative Example 1
[0131] The difference between this comparative example and Example 3 is that the step of preparing an inorganic crosslinking agent in step S1 is eliminated, and an equal amount of nano titanium dioxide particles are used to replace the inorganic crosslinking agent in the process of preparing the modified polyamide.
[0132] Comparative Example 2
[0133] The difference between this comparative example and Example 3 is that the step of preparing the modified capsules in step S2 is eliminated, and the self-repairing capsules are used in equal amounts to replace the modified capsules in the process of preparing the impregnation solution.
[0134] Comparative Example 3
[0135] The difference between this comparative example and Example 3 is that the step of preparing modified capsules in step S2 is eliminated, and an equal amount of nano-silicon dioxide particles are used to replace the modified capsules in the process of preparing the impregnation solution.
[0136] Performance Test:
[0137] The hydrostatic pressure of the waterproof tarpaulins prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to Standard FZ / T 14009-2014 "Dyed Vinylon Waterproof Canvas for Tarpaulins".
[0138] The self-repairing time of the waterproof tarpaulins prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard HG / T 5675-2020 "Self-repairing hardened film of optical functional film";
[0139] The volume abrasion loss of the waterproof tarpaulins prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard GB / T 9867-2008 "Determination of wear resistance of vulcanized rubber or thermoplastic rubber (rotating roller abrasion machine method)";
[0140] The limiting oxygen index of the waterproof tarpaulins prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard GB / T 2406.2-2009 "Determination of combustion behavior of plastics by oxygen index method Part 2: Room temperature test";
[0141] The ultraviolet transmittance of the waterproof tarpaulins prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard HG / T 4735-2014 “Determination of the anti-ultraviolet performance of textile dyeing and finishing auxiliaries and anti-ultraviolet finishing agents”. The specific data are shown in Table 1.
[0142] Table 1-Performance test data of each sample
[0143]
[0144] Data Analysis:
[0145] By comparing and analyzing the data in Table 1 above, the hydrostatic pressure of the waterproof tarpaulin prepared by the present invention is 54.2 kPa, the self-repair time is 7 min, and the volume wear is 29 mm. 3 , vertical burning grade is V-0 and UV transmittance is only 3.9%;
[0146] By comparing the data of Example 3 with that of Comparative Example 1, it can be found that the wear resistance of the waterproof tarpaulin is significantly reduced, indicating that the large number of amino groups on the surface of the modified cross-linking agent makes the prepared modified polyamide have a more complex spatial structure, which significantly improves the wear resistance of the material; by comparing the data of Example 3 with that of Comparative Example 1, it can be found that the self-repairing ability of the waterproof tarpaulin is significantly reduced, indicating that after the surface is modified with active functional groups, the self-repairing structure is more evenly distributed in the tarpaulin, which significantly improves the self-repairing ability of the material; by comparing the data of Example 3 with that of Comparative Example 1, it can be found that the hydrostatic pressure of the waterproof tarpaulin is significantly reduced, indicating that after the surface is modified with active functional groups, the modified capsules make the structure of the impregnating liquid more compact, which significantly improves the waterproof performance of the material, indicating that:
[0147] The present invention prepares an inorganic cross-linking agent and a modified capsule, and hybridizes the segment structures of the modified polyamide and the impregnating liquid respectively, so that the material structure is more compact, and the waterproof ability of the material is significantly enhanced. The triazine ring and the phosphoric acid structure of the modified polyamide segment improve the flame retardancy of the material. When the waterproof tarpaulin is structurally damaged, the modified capsule releases the repair material and the photoinitiator, and the repair material, the coating segment and the modified polyamide undergo a polymerization reaction under light, and finally the tarpaulin structure is repaired, thereby extending the service life of the tarpaulin.
[0148] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for recycling waste textiles to prepare high-strength rainproof tarpaulins, characterized in that: The following steps are involved: S1. Add modified polyamide, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, aluminum chloride and dimethyl sulfoxide into a reactor, raise the temperature of the reactor to 30-50° C., keep the temperature for 1-3 hours, post-treat to obtain phosphated polyamide, and then prepare a waterproof base fabric based on the phosphated polyamide through melt spinning, twisting, warping and weaving; S2, adding self-repairing capsules, 3-(methacryloyloxy)propyltrimethoxysilane, sodium hydroxide and deionized water into a reactor, raising the temperature of the reactor to 30-50° C., maintaining the temperature for 3-5 hours, and post-treating to obtain modified capsules; S3, adding 2-(perfluorohexyl)ethyl methacrylate, acrylic acid, triphenylethylene, modified capsules, azobisisobutyronitrile and dimethyl sulfoxide into a reaction kettle, raising the temperature of the reaction kettle to 70-80° C., keeping the temperature for reaction for 2-4 hours, and post-treating to obtain an impregnation solution; S4, immersing the waterproof base fabric into the modified waterproof coating, and obtaining the waterproof tarpaulin after dipping and rolling modification.
2. The method for preparing high-strength rainproof tarpaulin by recycling waste textiles according to claim 1, characterized in that: In step S1, the amount ratio of modified polyamide, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, aluminum chloride and dimethyl sulfoxide is 8-10g:2-3g:0.3-0.5g:30-50mL; in step S2, the amount ratio of self-repairing capsule, 3-(methacryloyloxy)propyltrimethoxysilane, sodium hydroxide and deionized water is 8-10g:2-3g:0.3-0.5 g:30-50mL; in step S3, the usage ratio of 2-(perfluorohexyl)ethyl methacrylate, acrylic acid, triphenylethylene, modified capsules, azobisisobutyronitrile and dimethyl sulfoxide is 5-8g:3-5g:2-3g:3-4g:0.5-0.8g:40-60mL; in step S4, the padding modification operation is a two-dip and two-pad process, the bath ratio is 1:20-25, and the padding rate is 90-110%.
3. The method for preparing high-strength rainproof tarpaulin by recycling waste textiles according to claim 1, characterized in that: In step S1, the preparation method of the modified polyamide comprises the following steps: A1. Add waste textiles into a pulverizer and grind them, then pass through a 400-600 mesh screen to obtain powder to be recycled; A2, adding the powder to be recycled, 2-vinyl-4,6-diamino-1,3,5-triazine, aluminum hydroxide and N,N-dimethylformamide into a high-pressure reactor, introducing nitrogen protection, raising the temperature of the reactor to 80-120°C, keeping the temperature for reaction for 2-4h, and post-treating to obtain the aminolysis fragment; A3. Add the aminolysis segment, fumaric acid, inorganic crosslinking agent, N,N'-dicyclohexylcarbodiimide, triethylamine and dimethyl sulfoxide into the reactor, increase the temperature of the reactor to 150-160°C, keep the reaction temperature for 1-2 hours, and post-treat to obtain modified polyamide.
4. The method for preparing high-strength rainproof tarpaulin by recycling waste textiles according to claim 2, characterized in that: In step A2, the amount ratio of the powder to be recovered, 2-vinyl-4,6-diamino-1,3,5-triazine, aluminum hydroxide and N,N-dimethylformamide is 8-10g:2-3g:0.3-0.5g:40-60mL; in step A3, the amount ratio of the aminolysis segment, fumaric acid, inorganic crosslinking agent, N,N'-dicyclohexylcarbodiimide, triethylamine and dimethyl sulfoxide is 5-8g:3-5g:2-3g:0.3-0.5g:0.5-0.8g:40-60mL.
5. The method for preparing high-strength rainproof tarpaulin by recycling waste textiles according to claim 3, characterized in that: In step S1, the method for preparing the inorganic crosslinking agent comprises the following steps: B1. Add zinc acetate dihydrate, ethanol and polyvinyl pyrrolidone into a reaction kettle, stir at room temperature for 20-30 minutes, adjust the pH value of the reaction system to 9-10 with protective ammonia water, continue stirring for 30-40 minutes to obtain a modified gel, and post-treat the nano zinc oxide particles; B2. Add nano zinc oxide particles, 3-aminopropyltriethoxysilane, sodium hydroxide and deionized water into a reactor, increase the temperature of the reactor to 30-50° C., keep the temperature for 3-5 hours, and post-treat to obtain an inorganic cross-linking agent.
6. The method for preparing high-strength rainproof tarpaulin by recycling waste textiles according to claim 4, characterized in that: In step B1, the usage ratio of zinc acetate dihydrate, ethanol and polyvinyl pyrrolidone is 3-5g:15-20mL:0.3-0.5g; in step B2, the usage ratio of nano zinc oxide particles, 3-aminopropyltriethoxysilane, sodium hydroxide and deionized water is 8-10g:2-3g:0.3-0.5g:40-60mL.
7. The method for preparing high-strength rainproof tarpaulin by recycling waste textiles according to claim 1, characterized in that: In step S2, the method for preparing the self-repairing capsule comprises the following steps: C1, adding 3-(methacryloyloxy)propyltrimethoxysilane, 3-amino-4,4,4-trifluorocrotonic acid ethyl ester, benzoin, 2,4,6-trimethylbenzoyldiphenylphosphine oxide and tetraethyl orthosilicate into a reaction kettle and stirring for 5-10 minutes to obtain a modified oil phase solution; C2, adding the modified oil phase solution into a high-speed homogenizer, and pouring the modified liquid into the modified oil phase solution, setting the speed of the high-speed homogenizer to 8000-9000 rpm, stirring at room temperature for 20-30 minutes, to obtain a modified emulsion; C3. Add the modified emulsion into the reactor and stir. Add 1-2 mol / L hydrochloric acid solution into the reactor to adjust the pH value of the system to 4-5. Raise the temperature of the reactor to 40-50°C. After keeping the temperature for 3-4 hours, add the supplement into the reactor. After keeping the temperature for 3-4 hours, add the supplement again. Keep the temperature for 8-12 hours. After post-treatment, obtain the self-repairing capsule.
8. The method for recycling waste textiles to prepare high-strength rainproof tarpaulin according to claim 1, characterized in that: In step S1, the method for preparing the waterproof base fabric comprises the following steps: D1, adding the phosphated polyamide and auxiliary materials into a twin-screw extruder for melt extrusion, and then extruding through a spinneret to obtain modified filaments; D2, twisting the modified filaments to obtain modified twisted yarns, and warping the modified twisted yarns to obtain modified warp yarns; D3, using modified warp yarn for weaving and post-processing to obtain a waterproof base fabric.
Citation Information
Patent Citations
Preparation method of composite waterproof coiled material with self-repairable surface layer
CN117586710A